The Role of Hydrogen in the Energy Transition - Martin Lambert; Bassam Fattouh (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2021)
The last two years have seen growing momentum behind the global recognition of the urgency of the 'climate emergency', with more and more countries committing to achieve net zero emissions. There has also been a growing conviction that hydrogen will play a significant role in the decarbonisation of the energy system. Electrification will certainly be very important, with many commentators suggesting that the share of electricity in final consumption is likely to rise from typically around 20 per cent today to around 50 per cent by 2050. Even if that proves to be an underestimate, it will still leave considerable demand for low-carbon molecules, and, with current technologies, the most likely low-carbon (or preferably zero-carbon) molecule is hydrogen. A growing number of countries have now published national hydrogen strategies, and more such strategies are under development. These strategies set bold ambitions for development of hydrogen but are relatively unclear on the pathways and steps to reach those ambitions. Low-carbon hydrogen is starting from a small base, and current costs do not support a commercial business case. For hydrogen to achieve the ambitious targets will require many players across the energy industry (private sector, government, regulators, and consumer groups) to work together to drive the required policies and behaviours. The structures to enable that collaboration will need to be developed as a matter of urgency in the next year or two. Against that background, it is very timely that this May 2021 edition of the Oxford Energy Forum is dedicated to exploring the role of hydrogen in the energy transition.
Keywords: 330